2001
DOI: 10.1089/15246090152636523
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Bone Mineral Density of Veiled and Unveiled Turkish Women

Abstract: The aim of the study is to compare vitamin D status and bone mineral density (BMD) in veiled and unveiled healthy Turkish women of reproductive age. Thirty young to middle-aged volunteer veiled women and 30 age-matched control subjects with western clothing habits were enrolled in the study. The two groups had similar dietary habits, body mass index (BMI) distribution, and gestational history. Physical and laboratory examinations were performed to rule out any disease that could affect bone metabolism. Serum 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
3
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 15 publications
7
65
3
11
Order By: Relevance
“…. There have been prevalence studies on 25(OH)D deficiency and/or insufficiency in the Turkish population 25 , and most have been performed on women, people in nursing homes, and the elderly [26][27][28] . Also, obesity leads to many health problems worldwide.…”
Section: Resultsmentioning
confidence: 99%
“…. There have been prevalence studies on 25(OH)D deficiency and/or insufficiency in the Turkish population 25 , and most have been performed on women, people in nursing homes, and the elderly [26][27][28] . Also, obesity leads to many health problems worldwide.…”
Section: Resultsmentioning
confidence: 99%
“…The high prevalence of vitamin D deficiency among women, youngsters and high school students, especially girls, has been found by recent studies in Isfahan and Tehran [33,34,35]. Although it has been found that veiled women have a low vitamin D status [36], a major changing lifestyle trend during the past decades, there is spread of urbanization, indoor living, air pollution, changes in diet, widespread use of sun screens, avoiding sun exposure for fear of skin cancer and concern about skin beauty, all of which are thought to cause vitamin D deficiency, with the latter two being more prevalent among females. Moreover, Iranian women spend less time in the sun, compared to men, which could also lead to vitamin D deficiency, but is independent of wearing a hijab or veil and therefore is mostly due to culture and lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…In general, vitamin D deficiency was prominent in people living in high latitudes, during the winter season, the use of sunscreens and people who wear cultural clothing such as veiling and concealing clothing. Concealed clothing blocks the absorbance of UV light therefore fails to produce vitamin D. Furthermore, Iranian women spend less time outdoor over men, which make them and their children more prone to the deficiency [31].…”
Section: Discussionmentioning
confidence: 99%